2015
DOI: 10.4209/aaqr.2015.02.0079
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics of Fine Particles Emitted from Different Chinese Cooking Styles

Abstract: Cooking process was regarded as one of the most significant contributor to fine particles (PM 2.5 ) in ambient atmosphere and its chemical characteristics would be great different among various cooking styles. In this study, PM 2.5 emitted from four different Chinese cooking styles, including Home cooking, Shandong cuisine, Hunan cuisine, and Barbecue, were collected using a dilution sampling system. Then, PM 2.5 mass concentrations were weighted, and its chemical composition were analyzed. It was found that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 38 publications
6
26
0
Order By: Relevance
“…F3 and F5 were recognized as indoor source (cooking and smoking) factors, where their contribution was 20.2%. Chemical elements in cooking fumes has been analyzed in several studies, and contents of Al, Zn, Mg and Ca were relatively high in PM 2.5 samples from different kitchens [ 41 , 42 , 43 ], and Zn was considered to be one of the most abundant metals in cooking fumes [ 41 , 43 ]. In this study, data of 14 houses without smoking and window opening in heating season were analyzed in Table 4 , and found that Zn and Ca may be related to indoor cooking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…F3 and F5 were recognized as indoor source (cooking and smoking) factors, where their contribution was 20.2%. Chemical elements in cooking fumes has been analyzed in several studies, and contents of Al, Zn, Mg and Ca were relatively high in PM 2.5 samples from different kitchens [ 41 , 42 , 43 ], and Zn was considered to be one of the most abundant metals in cooking fumes [ 41 , 43 ]. In this study, data of 14 houses without smoking and window opening in heating season were analyzed in Table 4 , and found that Zn and Ca may be related to indoor cooking.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we did not choose elements representing indoor cooking for multiple linear regression analysis. Though we collected some information related to indoor cooking, such as frequency of cooking, kitchen door and hoods used during sampling, etc., that was not enough because the concentrations of elements from indoor cooking can be greatly influenced by the cooking style, oils and foods used for cooking [ 41 , 42 ], and information about these variables were not collected in this study. Another reason is most of the houses in this study did indoor cooking during the sampling period, so the study lacked a certain number of non-cooking houses as a control to compare and analyze the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAH production from charbroiling cooking is a function both of the fat content of the meat and the proximity of the food to the heat source, and can be reduced by cooking for longer periods at lower temperatures (Phillips, 1999). Previous studies have shown that meat charbroiling processes exhibit higher PAH emissions than other cooking styles (McDonald et al, 2003;Wang et al, 2015).…”
Section: Pah and Nitro-pah Emissionsmentioning
confidence: 99%
“…For example, K can be used as a marker of cooking PM emissions. Other metals such as Fe, Cu, and nickel (Ni) can be leached from the stainless steel surfaces under high cooking temperatures (Wang et al, 2015) or even the control technologies themselves (e.g., the stainless steel in-hood cartridges utilized in CT1). Fig.…”
Section: Pah and Nitro-pah Emissionsmentioning
confidence: 99%